Radial Access for Lower Extremity Peripheral Arterial Interventions: Do We Have the Tools? - Posham, Raghuram (Semin Intervent Radiol, 2018)
The benefits of transradial arterial access (TRA) versus transfemoral arterial access (TFA) have been extensively described in the literature; however, TFA remains the predominant access site choice in the management of peripheral arterial disease (PAD). There are still significant unmet needs for operators wishing to provide the same effective interventions for lower extremity PAD via TRA as with TFA. This article provides an up-to-date review of the literature and devices currently available for operators wishing to treat lower extremity PAD via TRA and the limitations they may face.